Discovery of novel and potent safinamide-based derivatives as highly selective hMAO-B inhibitors for treatment of Parkinson's disease (PD): Design, synthesis, in vitro, in vivo and in silico biological studies - Elkamhawy, A.; Paik, S.; Park, J.-H.; Kim, H.J.; Hassan, A.H.E.; Lee, K.; Park, K.D.; Roh, E.J. (Academic Press Inc., 2021)
Up to date, the current clinical practice employs only symptomatic treatments for management of Parkinson's disease (PD) but unable to stop disease progression. The discovery of new chemical entities endowed with potent and selective human monoamine oxidase B (hMAO-B) inhibitory activity is a clinically relevant subject. Herein, a structural optimization strategy for safinamide (a well-known second generation hMAO-B inhibitor) afforded a series of thirty-six safinamide-derived new analogs (4aa？bj). Most compounds showed promising inhibitory activities against hMAO-B (>70% inhibition at a single dose concentration of 10 ？M), with no apparent effect on hMAO-A at 100 μM. Moreover, while six compounds (4ak, 4as, 4az, 4be, 4bg, and 4bi) exhibited potent double-digit nanomolar activities over hMAO-B with IC50 values of 29.5, 42.2, 22.3, 18.8, 42.2, and 33.9 nM, respectively, three derivatives (4aq, 4at, and 4bf), possessing the same carboxamide moiety (2-pyrazinyl), showed the most potent single-digit nanomolar activities (IC50 = 9.7, 5.1, and 3.9 nM, respectively). Compound 4bf revealed an excellent selectivity index (SI > 25641) with a 29-fold increase compared to safinamide (SI > 892). A structure activity relationship along with molecular docking simulations provided insights into enzyme ？ inhibitor interactions and a rational for the observed activity. In an in vivo MPTP-induced mouse model of PD, oral administration of compound 4bf significantly protected nigrostriatal dopaminergic neurons as revealed by tyrosine hydroxylase staining and prevented MPTP-induced Parkinsonism as revealed by motor behavioral assays. Accordingly, we present compound 4bf as a novel, highly potent, and selective hMAO-B inhibitor with an effective therapeutic profile for relieving PD. ？ 2021 Elsevier Inc.